The effects of COVID-19 on Airbnb - Boros, Lajos; Dudás, Gábor; Kovalcsik, Tamás (Hungarian Geographical Bulletin, 2020)
COVID-19 pandemic starting at the end of 2019, hit hard tourism and hospitality industries throughout the world. As a part of the processes, the most popular P2P accommodation service, the Airbnb also faced a rapid drop in bookings. This study explores and compares the effects of the first wave of the pandemic on the Airbnb markets of 15 cities. The analysis is based on the data retrieved from Insideairbnb.com. Booking trends are compared between 2019 and 2020 and a day-to-day analysis of occupancy rates during the first months of 2020 is also performed. Special attention was paid to the effects of pandemic on different price categories of listings. The results show that the evolution of local pandemic situation had the most significant impact on bookings and occupancy rates in the investigated cities. The characteristics of local markets and the pandemic and economic situation of sending countries had also great influence on the bookings and cancellations. In addition, in some cases the cancellations did not affect the reservations made for the later periods, meaning that tourists hoped for a quick recovery. The effect on price categories was also different from one location to another. The study provides empirical insights to the effects of the disease on P2P accommodations. Furthermore, the future of short-term rentals is also discussed briefly.